Introduction human geographies - Dombroski, Kelly; Goodwin, Mark; Qian, Juxi; Williams, Andrew; Cloke, Paul (London Routledge, 2024)
Introducing Human Geographies is a 'travel guide' into the academic subject of human geography and the things that it studies. The coverage of the new edition has been thoroughly refreshed to reflect and engage with the contemporary nature and direction of human geography. This updated and much extended fourth edition includes a diverse range of authors and topics from across the globe, with a completely revised set of contributions reflecting contemporary concerns in human geography.
Keywords: Geography; Earth sciences; Human geography